HUKUM, HAKIM, MAHKUM FIH DAN MAHKUM ALAIH (Studi Pemahaman Dasar Ilmu Hukum Islam) - Cut Ali, Isnu (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2021)
In the terms of the ushul scholars, law is defined as a khitabsyari 'which is related to the actions of mukallaf, whether they are thalab (demands), takhyiir (choice) or wadl'i (provisions). Meanwhile, law according to fiqh experts is a syar'i characteristic which is the influence of the khitab. Thus, the influence of Allah's khitab which implies the obligation to perform prayers from the verse "Aqiimu as-Sholaah" is a law. Essentially the judge is Allah Almighty. Simply, nothing else. The messengers of Allah only convey the message and the laws. They all did not create or enforce laws. Meanwhile the mujtahids were merely exposing the veils of the law. They are also not creators of Sharia law, even though by custom they are also sometimes called judges. What is meant by mahkumfih is the act of a mukallaf related to taklif / imposition. Taklif which comes from Allah is aimed at man in every one of his actions. Mahkumalaih is a mukallaf whose actions are related to the law of shari '.